In search of transparent networks. - Morris, A.S., III
Optical transmission networks work well, but their switchgear is opaque in that it must convert signals to electronic form before routing them. In this paper, the author presents a look at how the candidate technologies for all-optical, or transparent, switching work and stack up against each other
Keywords: All-optical switching; Candidate technologies; Electronic signal conversion; Optical transmission networks; Signal routing; Switchgear; Transparent switching